EMPOWERING SUSTAINABLE ECONOMIC DEVELOPMENT: ORGANIZATIONAL AND EMPLOYEE PERFORMANCE IN INDONESIA’S PRINTING INDUSTRY - Sadikin, Mochamad Rizki; Nugroho, Mario (Journal of Business Studies and Management Review, 2025)
This study investigates the impact of leadership style, motivation, and work environment on employee performance at a prominent printing company in Indonesia. The research utilized a census sampling method to select a sample of 52 permanent employees. Data were gathered via survey, with a structured questionnaire serving as the primary research instrument. Structural Equation Modeling (SEM) using Partial Least Squares (PLS) Version 4 software was employed for data analysis. The findings reveal that leadership style has a positive effect on employee performance. Similarly, the work environment positively influences both employee performance and motivation. Furthermore, motivation is positively related to employee performance. Conversely, the study found that leadership style does not have a direct impact on motivation. These results underscore the importance of a supportive work environment and intrinsic motivation in enhancing employee performance, while suggesting that leadership style’s impact on performance does not extend directly to motivational aspects